Effect of conventional diuretics versus conventional diuretics plus mannitol on electrolytes for the treatment of cirrhotic ascites (Bangladesh Medical Journal, 2016)
Ascites is the most frequent finding of decompensated liver cirrhosis. Mannitol may be used with conventional diuretics for increase urinary volume for the treatment of cirrhotic ascites. This case control study was done in the Department of Medicine, Sere-Bangla Medical College &Hospital, Barisal from July 2009 to June 2011. No electrolyte imbalance was seen by conventional diuretics plus mannitol for the treatment of cirrhotic ascites. Mannitol did not causee lectrolyte imbalance & may be used with conventional diuretics for the treatment of cirrhotic ascites as it increased the urinary volume.Bangladesh Med J. 2016 May; 45 (2): 90-93